The German Debt Brake: Approaches for an Improvement of the Technical Design - Thomas Lenk; Christian Bender; Philipp Glinka (Vierteljahrshefte zur Wirtschaftsforschung, 2020)
This article examines the German debt brake from a technical point of view. By designing the debt brake on the basis of the EU method, it should be possible to achieve an adequate division between the cyclical and structural components of the budget balance, while at the same time pursuing a countercyclical fiscal policy. However, recent studies suggest that the mechanics of the debt brake are of a rather pro-cyclical in nature. This paper focuses on the behavior of the NAWRU – a central element of the production function approach – as well as revisions, which both seem to be a source of a pro-cyclical influence towards the German debt brake. Additionally, reform proposals are outlined which show that a change of the Basic Law is not necessary in order to improve the dynamics of the fiscal rule at hand. – – Der Artikel untersucht die deutsche Schuldenbremse von einem technischen Standpunkt aus. Mit der Ausgestaltung der Schuldenbremse anhand der EU-Methode sollte eine adäquate Aufteilung zwischen der konjunkturellen und der strukturellen Komponente des Budgetsaldos gelingen und dabei antizyklische Fiskalpolitik möglich sein. Aktuelle Studien zeigen jedoch, dass die Mechanik der Schuldenbremse eher pro-zyklischer Natur ist. Dieser Beitrag thematisiert die Verhaltensweise der NAWRU – ein zentrales Element des Produktionsfunktionsansatzes – wie auch Revisionen, welche eine Quelle pro-zyklischen Einflusses auf die deutsche Schuldenbremse darstellen. Darüber hinaus werden Reformoptionen dargestellt, welche aufzeigen, dass eine Änderung des Grundgesetzes nicht notwendig ist, um die Sachgerechtigkeit der betrachteten Fiskalregel zu verbessern.
Keywords: C10; C40; C82; H20; H30; H60; H62; H63; 330; German debt brake; NAWRU; cyclicality; budget balance; stuctural balance; reform